a) 2x + 1 = x + 6 b) 2 - 3x = x + 14
2.1
ItzSavitar:
não faco a menor ideia, por isso n coloquei ele, quando a pessoa corrigir eu respondo junto com o 2.1
Soluções para a tarefa
Respondido por
4
Explicação passo-a-passo:
A) 2x + 1 = x + 6
2x - x = 6 - 1
x = 5
B) 2 - 3x = x + 14
2 - 14 = x + 3x
-12 = 4x
-12 ÷ 4 = x
-3 = x
Perguntas interessantes
Ed. Física,
9 meses atrás
Geografia,
9 meses atrás
Artes,
9 meses atrás
Inglês,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás